KONTRIBUSI PENELITI DALAM MENUNJANG FUNGSI KELITBANGAN BADAN PERENCANAAN, PENELITIAN DAN PENGEMBANGAN DAERAH (BAPPEDA) PROVINSI BENGKULU - Harwindah Harwindah (Khazanah Intelektual, 2020)
This study aims to determine how much the contribution of researchers in supporting the development function of the Bengkulu Province Planning, Research and Development Agency (Bapelitbangda). This type of research is a qualitative analysis with a descriptive approach. The focus of the research is the output of Bapelitbangda Bengkulu Province and the output of the researcher's performance through the assessment of SKP. The results showed that the contribution of researchers to the unit output was 22.2%; while the performance output at SKP is 7 (seven) researchers, there are 5 (five) researchers whose work results are not achieved based on the proposed work objectives. This indicates the low contribution of researchers to the development function of the Regional Planning, Research and Development Agency (Bapelitbangda) Bengkulu Province.